Transmission Cooperative Strategies for MIMO-OFDM Heterogeneous Networks - Ali, S.S. (2017)
Mobile traffic in cellular networks is increasing exponentially, mainly due to the use of data intensive services like video. One way to cope with these demands is to reduce the cell-size by deploying small-cells along the coverage area of the current macro-cell system. The deployment of small-cells significantly improves indoor coverage. Nevertheless, as additional spectrum licenses are difficult and expensive to acquire it is expected that the macro and small-cells will coexist under the same spectrum. The coexistence of the two systems results in crosstier/ inter-system interference. In this context, we design several interference alignment based techniques for the downlink of heterogeneous networks, in order to cancel the interference generated from macro-cell at small-cell user terminals. More specifically, in this contribution we design interference alignment methods under different levels of inter-system coordination and the constraint that the performance of macro-cell system is kept close to the case where small-cell system is switched-off. Numerical results demonstrate that the proposed methods achieve close to the optimal performance with low overhead